Occurrence of per- and polyfluoroalkyl substances (PFASs) in wastewater of major cities across China in 2014 and 2016. (September 2021) - Lu, Yintao; Gao, Jianfa; Nguyen, Hue T.; Vijayasarathy, Soumini; Du, Peng; Li, Xiqing; Yao, Hong; Mueller, Jochen F.; Thai, Phong K.
Abstract: China produced and consumed a large amount of per- and polyfluoroalkyl substances (PFASs). whose persistency and possible toxicity to organisms have raised public health concerns. Analyzing influent wastewater could help to assess the composition and mass load of PFASs discharged into a wastewater treatment plant (WWTP) from its catchment. In this study, we analyzed 27 PFASs in wastewater samples collected from 42 WWTPs across China in 2014 and 2016. Results indicated that perfluorobutanoic acid (PFBA), perfluorohexanoic acid (PFHxA), perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) were the most common PFASs in wastewater. Population normalized mass loads of PFOA and PFOS were higher in Eastern China than in the other three regions, possibly due to their higher usage. Although the concentrations of PFASs in Central and West areas were showed lower than in East area, Wuhan (in Central area) and Lanzhou (in West area) were hotspots of PFASs pollution because of their industry structure. Population density and per capita Gross Domestic Product (GDP) have positive correlations with the concentration of PFBA, PFOA, PFHxA, and ∑ PFASs in wastewater. The estimated annual release of PFASs to WWTPs in our study is much lower than the total emission to the environment. Our results suggest that although there was some reduction in the production volume, certain legacy PFASs were still released into wastewater and their composition and concentration vary among WWTPs. Graphical abstract: Image 1 Highlights: Short-chain PFASs have higher detection frequency than long-chain ones except PFOS and PFOA. Higher concentration of PFOA and PFOS in East China than other regions. PFASs composition and concentration vary among WWTPs. Positive correlation between per capita GDP, population density and concentration of certain PFASs.